Competência tributária: entre tipos e conceitos - Torrezan Júnior, Osvaldo Madinor (2023)
This dissertation aims to analyze, through bibliography and case studies, whether the contents contained in the words that discriminate constitutional tax powers have a typological or conceptual perspective, in order to identify whether there is a possibility of adapting constitutional rigidity to the increasingly rapid change in social reality, in a context of constant digitalization of the economy. In order to do so, the work is divided into three chapters. In the first, the main modern philosophical conceptions about Law are addressed, concluding that the science of tax law, in Brazil, was deeply influenced by positivist thinking, which resulted in the predominance of a doctrine that was too focused on the rigor of language, but oblivious to the evolution of events occurring in society. In the second, the history and purpose of the discrimination of constitutional rules of competence are explained in detail to identify whether the material criteria listed in the Constitution should be more adequately understood as types or as concepts. In the third, some paradigmatic judgments handed down by the Federal Supreme Court are critically examined, in which the Court faced the theme exposed in the previous chapters. In the end, it is concluded that the constituent adopted the use of types and attributed it to the complementary law, through art. 146, I, of the Federal Constitution, the role of resolving tax conflicts and that article 110 of the National Tax Code cannot be used to define the content of the rules of jurisdiction.